Infection prevention and control knowledge among health sciences students: a cross-sectional study from Malaysia - Nahas, Abdul Rahman Fata; Samsuri, Hanis Zulaikha; Akkawi, Muhammad Eid; Elnaem, Mohamed Hassan; El Sayed, Tarek; Mohd Taufek, Nor Hidayah; Mohammed Al-Shami, Abdulkareem (IIUM Press, 2024)
Introduction: Infection prevention and control (IPC) is a crucial component of the healthcare system that demands adherence to standards to avoid and reduce the risk of infectious diseases spreading among patients, staff members, and visitors to healthcare institutions. The aim of this study was to assess IPC knowledge among undergraduate health sciences students and to identify the critical IPC components that need to be addressed.